Osteogenesis and Bone Regeneration - Yang, Haisheng (IntechOpen, 2019)
Osteogenesis is a core component of the skeletal system and depends on the well-coordinated proliferation and differentiation of osteogenic cells. Multiple signaling pathways and transcriptional factors tightly regulate the process of osteogenesis. Any abnormities in bone formation could cause severe disorders such as osteogenesis imperfecta and osteoporosis. Bone regeneration, a complex and well-orchestrated physiological process of osteogenesis, remains a medical challenge in the field of orthopedics and maxillofacial surgery. This book provides an overview of the current developments in osteogenesis and bone regeneration, including molecular and cellular mechanisms, physical therapies (low-level laser, distraction osteogenesis), biological therapies (mesenchymal stem cells, stem cell derived exosomes, inflammatory factor, Chinese medicine), as well as tissue engineering approaches promoting bone regeneration by targeting osteogenesis.